2004
DOI: 10.1101/lm.85404
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of nondeclarative sequence learning in mice: Development of an animal analog of the human serial reaction time task: Figure 1.

Abstract: In this paper, we demonstrate nondeclarative sequence learning in mice using an animal analog of the human serial reaction time task (SRT) that uses a within-group comparison of behavior in response to a repeating sequence versus a random sequence. Ten female B6CBA mice performed eleven 96-trial sessions containing 24 repetitions of a 4-trial sequence. During the 12th session, the repeating sequence was replaced with the random sequence halfway through the session. Reaction time (RT) to respond to an illuminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…These findings join a number of other demonstrations using the SRT procedure with nonhumans in which evidence has emerged of decreases in latencies during pattern training and increases during a random test (in rats: Christie & DalrympleAlford, 2004;Domenger & Schwarting, 2005; in mice: Christie & Hersch, 2004;in rhesus macaques: Procyk, Dominey, Amiez, & Joseph, 2000;in pigeons: Froehlich, Herbranson, Loper, Wood, & Shimp, 2004, Herbranson & Shimp, 2008Herbranson & Stanton, 2011;in Bengalese finches: Yamazaki, Suzuki, Inada, Iriki, & Okanoya, 2012). These studies have demonstrated that some learning occurs in nonhumans when reinforcement is randomly presented.…”
supporting
confidence: 49%
“…These findings join a number of other demonstrations using the SRT procedure with nonhumans in which evidence has emerged of decreases in latencies during pattern training and increases during a random test (in rats: Christie & DalrympleAlford, 2004;Domenger & Schwarting, 2005; in mice: Christie & Hersch, 2004;in rhesus macaques: Procyk, Dominey, Amiez, & Joseph, 2000;in pigeons: Froehlich, Herbranson, Loper, Wood, & Shimp, 2004, Herbranson & Shimp, 2008Herbranson & Stanton, 2011;in Bengalese finches: Yamazaki, Suzuki, Inada, Iriki, & Okanoya, 2012). These studies have demonstrated that some learning occurs in nonhumans when reinforcement is randomly presented.…”
supporting
confidence: 49%
“…The performance of more complex cognitive tasks (e.g., Christie & Hersch, 2004;Leenaars et al, 2012;McCoy et al, 2007) may be more sensitive to disturbance by prolonged (shift)work. When mainly interested in the effect of motivation on task performance, a different type of task could be preferable, for example, a task implementing ratio lever pressing or imposing delays.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that included children younger than age 12 years of age yielded inconsistent results, with some Wndings suggesting that sequence learning continues to develop until age 12. However, it is important to keep in mind that even pigeons, rats, and mice show evidence of sequence learning (Bailey & Mair, 2006;Christie & Dalrymple-Alford, 2004;Christie & Hersch, 2004;Froelich, Herbranson, Loper, Wood, & Shimp, 2004). Thus, before concluding that spatial sequence learning is a higher cognitive skill requiring cortical maturation, it is crucial to conduct developmental studies spanning the period from infancy to 12 years of age to address methodological questions and to obtain a better understanding of the development of diVerent aspects of spatial sequence learning.…”
Section: Developmental Changes In Incidental Learningmentioning
confidence: 98%